America's deadliest election eaudiobook The cautionary tale of the most violent election in american history. - Bash, Dana (Harlequin Audio, 2024)
"Let chaos come." The violent election of 1872 that serves as a warning for today's divided politics. From CNN's Chief Political Correspondent Dana Bash, the fast-paced story of the extraordinary election that led to hundreds of murders, warfare in the streets of New Orleans, two governors of Louisiana — and changed the course of politics in our country. The Election of 1872 was the most contentious in American history. After both parties complained of corruption, neither candidate would concede, two governors claimed office and chaos erupted. Rival newspapers engaged in a bitter war of words, politicians plotted to overthrow the government, and their supporters fought in the streets and attempted assassinations. The entire country watched in grim fascination as the wounds of the Civil War were ripped open and the promise of President Grant's Reconstruction faltered in the face of violent resistance and the birth of the Ku Klux Klan. In this riveting book, Dana Bash and David Fisher tell the incredible, little-known story of the election that pushed democracy to the breaking point, and sparked historic events including: The Colfax Massacre, in which at least 150 Black men were killed by white supremacists The extraordinary train race from New York to New Orleans for control of the state government The election of the first black Congressman from Louisiana in the face of violent resistance The Supreme Court ruling that ended Reconstruction and became the foundation of Southern segregation, changing the American legal system for the next century Readers will find eerie parallels to today's divided political landscape and leaders willing to seize power no matter the cost. An eye-opening warning of what's at stake and what it takes to protect our democracy, this is a must-read tale of America's deadliest election.